COMMUNITY SERVICE OF IMMIGRATION POLYTECHNIC CADETS ON FIRE DISASTER VICTIMS IN THE WORK AREA OF IMMIGRATION OFFICE CLASS II BORDER CONTROL TANJUNG BALAI - M. Andhika Arya Rifansyah; Bobby Briando (Jurnal Abdimas Imigrasi, 2021)
Community dedication activities are routine activities carried out while undergoing LATJAPURA (Latihan Kerja Bhumi Pura) to bring Immigration Polytechnic Cadets closer to all levels of society, one of which is by giving support and assistance to community members who are affected by disasters. In this case, 5 Immigration Polytechnic cadets distributed aid directly to the victims of the fire disaster in the working area of the Class II TPI Immigration Office of Tanjung Balai. This activity aims as a sense of sensitivity and concern for the community and creates a positive impression to the Immigration Polytechnic.